What lies ahead? Consumer expectations and wishes for organic animal farming: analyzing improvements to boost confidence in organic livestock farming - Bayer, Elisa; Kühl, Sarah (Frontiers in Animal Science, 2024)
IntroductionTo meet the policy target of increasing the share of organic farming in the EU to 25% by 2030, it is also essential to increase consumer demand for organic products. For many consumers, animal welfare is one of the main reasons to buy organics. Trust is inherently important when purchasing organic food, as most of the standards on which organic farming relies, such as more space, cannot be verified by the consumer. Consumer trust in organic animal farming is therefore an important factor in the expansion of the market share of organic products. The aim of this study is to identify specific trust-building “changes” in organic livestock husbandry to strengthen consumer trust in the long term.MethodA total of eight regulations or practices, e.g. early cow-calf separation or regulations on the use of antibiotics, were assessed in terms of consumer awareness. Further described changes to these practices or regulations were ranked regarding their potential to improve trust in organic animal husbandry.ResultsThe results show that most of the regulations and practices mentioned were not known to consumers, confirming a low level of consumer knowledge about specific aspects of organic farming. All eight possible changes would increase consumer trust, at least somewhat.DiscussionThe ranking shows that, in particular, the practice of dam rearing and an even stronger limitation of flock sizes for poultry have the highest potential to increase consumer trust in organic animal husbandry and can therefore be recommended as important strategies to meet consumer demands in the future.